Evaluation Des Conditions De Traitement Et De Stockage Des Plantes Médicinales Sur Les Marchés Du District d’Abidjan (Côte d’Ivoire) - Bernadin, Kouamé Kouassi; Witabouna, Koné Mamidou (European Scientific Journal, ESJ, 2017)
The present study was carried out to inventory medicinal plants storage conditions on the markets of Abidjan district. A survey was conducted from August to October 2015 in three settings of the district of Abidjan (Abobo, Adjame and Yopougon). A total of 350 sellers of medicinal plants were interrogated using semi-structured interviews. The respondents were predominantly female (98.9%), aged between 30 and 60 years. The supply of medicinal plants in the markets was done by the wholesalers (86%) who themselves harvested plants in different forests or savanah of Côte d’Ivoire. The majority of sellers (73%) did not apply any measure of hygiene in storage. These people in 99.4% of case were not trained on good storage practices. Sale places were accessible to rodents and exposed to dust caused by traffic jamp. The presence of mud (9.1%) and garbage (23.1%) was noted in the immediate surrounding of the displays. These practices of processing and storage of medicinal plants were similar in all the visited settings. These storage conditions may constitute a hazardous risk for the consumer and justify the degradation of medicinal plants on the markets.